2001
DOI: 10.1016/s0002-9440(10)61698-7
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-2 Is Associated with Tenascin-C in Calcific Aortic Stenosis

Abstract: We previously showed that the expression of tenascin (TN-C), an extracellular matrix glycoprotein found in developing bone and atherosclerotic plaque, and ma- The mechanism of calcific aortic stenosis has been investigated in clinical-pathological studies, that have demonstrated cuspal calcific deposits to be associated with mineralization of devitalized cells and subcellular vesicles, 1,2 as well as the deposition of extracellular matrix (ECM) proteins commonly present in bone.3 A number of ECM proteins norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
100
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(117 citation statements)
references
References 30 publications
(27 reference statements)
11
100
0
5
Order By: Relevance
“…12 They also contain tenascin C, 66 an extracellular matrix glycoprotein found in developing bones. 66 Recently, groups have isolated a subset of valvular fibroblasts that express osteoblast markers 57,65 and spontaneously form hydroxyapatite-containing calcified nodules in vitro.…”
Section: Calcificationmentioning
confidence: 99%
See 2 more Smart Citations
“…12 They also contain tenascin C, 66 an extracellular matrix glycoprotein found in developing bones. 66 Recently, groups have isolated a subset of valvular fibroblasts that express osteoblast markers 57,65 and spontaneously form hydroxyapatite-containing calcified nodules in vitro.…”
Section: Calcificationmentioning
confidence: 99%
“…12 They also contain tenascin C, 66 an extracellular matrix glycoprotein found in developing bones. 66 Recently, groups have isolated a subset of valvular fibroblasts that express osteoblast markers 57,65 and spontaneously form hydroxyapatite-containing calcified nodules in vitro. 57,65 In response to oxidized cholesterol, 57 transforming growth factor (TGF) ␤1, 57 BMP2, 57 and RANKL, 65 these cells increase their expression of osteoblast markers and increase their rate of calcified nodule formation.…”
Section: Calcificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Streptococcus pyogenes throat infection triggers an inflammatory reaction that involves several proinflammatory cytokines, such as tumor necrosis factor-α (TNFα), IL-1, and IL-6 (5). Immunohistochemical studies have shown expression of TnC in patients with congenital aortic valve stenosis (9,10). Moreover, a recent study reported that TNFα, interferon gamma (IFNγ) and TnC concentrations in patients with rheumatic HVD were significantly higher than those with congenital valvular malformation and normal controls.…”
Section: Introductionmentioning
confidence: 99%
“…Молекулярно-генетические механизмы процессов фиброза и ремоделирования МКМ при АС Механизмы ремоделирования МКМ при АС были изучены на примере ММР и катепсинов, ферментов, участвующих в деградации межклеточного матрикса: ММР 1,2,3,7,9,12 и их ингибиторов (TIMP1,2,3,4), катепсинов S, K, V, G, трансформирующего фактора роста β1(TGFβ1) [16,[48][49][50], TNF-α [51], тенасцина С [52]. Генетические полиморфизмы ММР и катеп-синов не изучались, однако высокий уровень экс-прессии гена ММР (в частности, ММР 1,7,9,12) и ТИМР 1,2 в образцах самих клапанов при морфоло-гическом исследовании был ассоциирован с АС [21].…”
Section: кальциевый обменunclassified